Abduction of Generalizations - Gauderis, Tjerk; Van De Putte, Frederik (THEORIA. An International Journal for Theory, History and Foundations of Science, 2012)
Abduction of generalizations is the process in which explanatory hypotheses are formed for an observed, yet puzzling generalization such as ``pineapples taste sweet" or ``rainbows appear when the sun breaks through the rain". This phenomenon has received little attention in formal logic and philosophy of science. The current paper remedies this lacuna by first giving an overview of some general characteristics of this process, elaborating on its ubiquity in scientific and daily life reasoning. Second, the adaptive logic $\LAG$ is presented to explicate this process formally.